Survey Responses of School Closures During the COVID-19 Outbreak in Taiwan - Chao, Kuo-Yu; Hsiao, Tung-Yuan; Cheng, Wei (Frontiers in Public Health, 2022)
Background Taiwan faced a surge of COVID-19 infections in May 2021. Because new cases were quickly increasing, parents called for school closures. A national parent group used an online survey to collect opinions about upcoming school closings planned by the Ministry of Education. This study evaluated the results of the survey for all respondents and investigated the level of viral transmission following school closures among students in Taiwan. Methods An online survey titled “Survey of Opinions of School Closures during the Current COVID-19 Outbreak” (SOSC-COVID-19) was designed by the national parent association and then distributed to members of the community throughout Taiwan via local parent groups from May 17 to 18, 2021. The survey included an open-ended respondents' opinions about school closures. Differences among regions and socioeconomic scores (SES) were analyzed with chi-square tests. Results A total of 8,703 completed survey forms data were analyzed. Nearly all respondents (7,973, 91.6%) approved of school closures; there were no differences of opinions inside and outside municipalities or by regional SES scores. Only 8.4% of respondents were opposed to any type of school closure, believing parents should decide whether their child attended school, which also did not vary with region or SES score. Qualitative feedback from parent and teacher responders indicated students' health and economic impacts were additional concerns that influenced their choice of whether the government or parents should decide about school closures. On the afternoon of May 18, 2021, the government of Taiwan closed all schools. Although a spike in new cases of COVID-19 occurred among students 10 days after school closures, over the next 40 days new cases declined, falling to zero by July 5th. Conclusions Despite the inability of nationwide school closures to completely halt transmission of the virus within families during the COVID-19 outbreak, school closures helped to impede transmission between students.